Lightfield hyperspectral imaging in neuro-oncology surgery: an IDEAL 0 and 1 study - MacCormac, Oscar; Noonan, Philip; Janatka, Mirek; Horgan, Conor C.; Bahl, Anisha; Qiu, Jianrong; Elliot, Matthew; Trotouin, Théo; Jacobs, Jaco; Patel, Sabina; Bergholt, Mads S.; Ashkan, Keyoumars; et al. (Frontiers in Neuroscience, 2023)
Introduction: Hyperspectral imaging (HSI) has shown real promise in the field of intra-operative imaging and tissue differentiation as it carries the capability to provide real-time information invisible to the naked eye whilst remaining label free. Previous iterations of intra-operative HSI systems have shown limitations, either due to carrying a large footprint limiting ease of use within the confines of a neurosurgical theatre environment, having a slow image acquisition time, or by compromising spatial/spectral resolution in favour of improvements to the surgical workflow. Lightfield hyperspectral imaging is a novel technique that has the potential to facilitate video rate image acquisition whilst maintaining a high spectral resolution. Our pre-clinical and first-in-human studies (IDEAL 0 and 1 respectively) demonstrate the necessary steps leading to the first in-vivo use of a real-time lightfield hyperspectral system in neuro-oncology surgery. Methods: A lightfield hyperspectral camera (Cubert Ultris X50) was integrated in a bespoke imaging system setup so that it could be safely adopted into the open neurosurgical workflow whilst maintaining sterility. Our system allowed to capture in-vivo hyperspectral data (155 bands, 350-1000nm) at 1.5Hz. Following successful implementation in a pre-clinical setup (IDEAL 0), our system was evaluated during brain tumour surgery in a single patient to remove a posterior fossa meningioma (IDEAL 1). Feedback from the theatre team was analysed and incorporated in a follow-up design aimed at implementing an IDEAL 2a study. Results: Focusing on our IDEAL 1 study results, hyperspectral information was acquired from the cerebellum and associated meningioma with minimal disruption to the neurosurgical workflow. To the best of our knowledge, this is the first demonstration of HSI acquisition with 100+ spectral bands at a frame rate over 1Hz in surgery. Disscussion: This work demonstrated that a lightfield hyperspectral imaging system not only meets the design criteria and specifications outlined in an IDEAL-0 (pre-clinical) study, but also that it is capable of translating into clinical practice as illustrated by a successful first in human study (IDEAL 1). This opens doors for further development and optimisation, given the increasing evidence that hyperspectral imaging can provide live, wide-field, and label-free intra-operative imaging and tissue differentiation.